Peran Manajemen Model Intelektual SDM dalam Meningkatkan Kinerja Organisasi Berkelanjutan - Sri Rachmi Nadhifah Dewi; Udisubakti Ciptomulyono; Gogor Arif Handiwibowo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid development of digital technology and globalization demands that companies not only pursue short-term economic profits but also focus on implementing technology and environmental sustainability. This study aims to analyze the role of Sustainable Intellectual Capital in improving Sustainable Performance in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study will also examine the role of E-Business Entrepreneurial Orientation in mediating the relationship between Sustainable Intellectual Capital and Sustainable Performance. The research method used is a quantitative method with data obtained through an online questionnaire with MSME owners or managerial teams as respondents. The data analysis technique used Structural Equation Modeling (SEM) to test the hypothesis and mediation effect. The results of the study indicate that Sustainable Intellectual Capital has a positive effect on Sustainable Performance and E-Business Entrepreneurial Orientation. Strong Sustainable Intellectual Capital has been proven to be able to encourage the formation of a more rapid E-Business Entrepreneurial Orientation and is able to accelerate the achievement of sustainable performance through technology-based innovation. These results confirm that E-Business Entrepreneurial Orientation has a strategic role, namely being able to support MSMEs in optimizing the potential of their Human Resources (HR) in facing digital market uncertainty by building competitive advantages that are in line with the principles of sustainability.